2021
DOI: 10.1186/s12872-021-01905-x
|View full text |Cite
|
Sign up to set email alerts
|

Body roundness index is a superior indicator to associate with the cardio‐metabolic risk: evidence from a cross‐sectional study with 17,000 Eastern-China adults

Abstract: Background To investigate the ability of body shape index (ABSI), body roundness index (BRI), waist circumference (WC), body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and body adiposity index (BAI) for predicting non-adipose cardio-metabolic risk. Methods A total of 17,360 Chinese subjects aged 18–95 years old who escaped cardiovascular disease (CVD) or diabetes were recruited in the cross-sectional study. Anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 76 publications
1
26
0
1
Order By: Relevance
“…Our results found that BRI showed good ability in identify clustered CMRFs, while it failed to recognize hyperglycemia in 7-17 age group, and could not distinguish dyslipidemia in two age group. In addition, we noticed that in correlation analysis among anthropometric indicators showed the coefficients between WHtR and BRI were 0.996-0.997 (P<0.001), which means these two indicators are strong correlation, the AUCs for single or clustered CMRFs of WHtR and BRI were exactly same in each age group, and the ROC curves of the two indicators were also completely overlapped, study in adults shows the same ability in screen CMRFs (19,34,35). However, Chang et al (17) found BRI performed better in predicting the presence of left ventricular hypertrophy (LVH) than BMI, WC and WHtR.…”
Section: Discussionmentioning
confidence: 85%
“…Our results found that BRI showed good ability in identify clustered CMRFs, while it failed to recognize hyperglycemia in 7-17 age group, and could not distinguish dyslipidemia in two age group. In addition, we noticed that in correlation analysis among anthropometric indicators showed the coefficients between WHtR and BRI were 0.996-0.997 (P<0.001), which means these two indicators are strong correlation, the AUCs for single or clustered CMRFs of WHtR and BRI were exactly same in each age group, and the ROC curves of the two indicators were also completely overlapped, study in adults shows the same ability in screen CMRFs (19,34,35). However, Chang et al (17) found BRI performed better in predicting the presence of left ventricular hypertrophy (LVH) than BMI, WC and WHtR.…”
Section: Discussionmentioning
confidence: 85%
“…External replication was performed using a targeted metabolomics approach in a sub-population of the Zhejiang Metabolic Syndrome Cohort, namely Xiazhi sub-cohort (N=1420). According to the same MetS criterion adopted in the untargeted metabolomics [19], 149 MetS patients and 253 controls were included into the external replication dataset. The detailed sample selection process has been described in the supplementary materials.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…It is possible that newer anthropometric indices such as the body roundness index may have produced a different result. 27 Physical activity and diet were not estimated, and it is possible that inclusion of these metrics may have altered the findings.…”
Section: Limitationsmentioning
confidence: 99%
“…It is possible that newer anthropometric indices such as the body roundness index may have produced a different result. 27 …”
Section: Limitationsmentioning
confidence: 99%